Pengaruh Leverage, Pertumbuhan Penjualan, CSR, dan Profitabilitas Terhadap Tax Avoidance - Putri Nurma Sari; Nadya Eka Putri; Elok Heniwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to examine the effect of leverage, sales growth, CSR, and profitability on tax avoidance in Primary Consumer Goods companies in the Agricultural Food Products, Beverages, and Primary Goods Retail Trade industries listed on the Indonesia Stock Exchange for the period 2020-2023. Tax avoidance is an effort by a company to minimize its tax burden legally. The variables were measured using the following methods: tax avoidance was proxied using the Effective Tax Rate (ETR) ratio, leverage was measured using the Debt to Equity Ratio (DER), sales growth was calculated using the annual revenue growth ratio, CSR was measured based on the number of disclosures compared to 66 indicators in accordance with POJK, while profitability was proxied using Return on Assets (ROA). This study uses a quantitative approach with multiple linear regression analysis. Data were obtained from the companies' annual financial reports and processed using E-Views software. The results show that leverage and profitability affect tax avoidance, while sales growth and CSR do not affect tax avoidance. These findings indicate that the higher a company's leverage and ROA, the greater its tendency to engage in tax avoidance.